Diagnosis of solid waste collection in a neighborhood in Mexicali, Mexico (International Seven Journal of Multidisciplinary, 2024)
This work is part of a research project being carried out by the team described above. It was developed in the Valle de Puebla neighborhood in Mexicali, B.C. The results of a survey carried out in that neighborhood are presented, they mention that the service is not constant, they do not know when the garbage truck passes by, they do not have a representative of the neighborhood before the city council and when it passes by, many times they are asked for a fee for picking up the garbage. This situation becomes an image and public health problem because when the cleaning service is not constant, the neighbors take out their garbage and the stray dogs spill it on the street, causing environmental contamination and harmful fauna.